Experimental Evidence of Chloride‐Induced Trap Passivation in Lead Halide Perovskites through Single Particle Blinking Studies. Issue 23 (24th April 2021) - Jin, Handong; Steele, Julian A.; Cheng, Ruolin; Parveen, Nagma; Roeffaers, Maarten B. J.; Hofkens, Johan; Debroye, Elke
Abstract: Research into organic–inorganic lead halide perovskites as photoactive material in solar cells and other electro‐optical devices has made immense progress in recent years. However, efficiency losses resulting from deep traps associated with framework defects, still limit the performance of perovskite semiconductors. Defect passivation by the incorporation of dopants, such as chloride doping in methylammonium lead iodide (MAPbI3 ) perovskite, is stated as one of the most efficient ways to reduce trap densities. Commonly used parameters like improved photoluminescence (PL) quantum yields and extended PL lifetimes provide nonconclusive experimental evidence on trap density suppression by chloride doping. In this work, the effect of chloride doping on the crystal morphology, composition, and PL of MAPbI3 nanocrystals is carefully investigated. Besides the anticipated enhanced PL intensity and extended PL lifetime, single‐particle PL intermittency studies reveal brighter and longer ON‐states with increasing amounts of chloride doping, which represents additional evidence of effective chloride‐induced trap passivation. These findings provide important guidelines for generating lead halide perovskite materials with significantly reduced trap densities toward the fabrication of high‐performance optoelectronic devices. Abstract : Incorporation of chloride dopants has been reported to be an effective method to passivate the trap densities in methylammonium lead iodide nanoparticles by demonstrating an enhanced photoluminescence (PL) intensity and extended PL lifetime. In this work, single particle PL intermittency studies revealing more bright and longer ON‐states with increasing amounts of chloride doping, represent additional evidence of effective chloride‐induced trap passivation.